SEMIOTIKA AYAT-AYAT KAUNIYAH ALQURAN SEBAGAI MEDIA KOMUNIKASI DAKWAH DALAM PERSPEKTIF PENDIDIKAN ISLAM - SOLCHAN GHOZALI (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
there is a balance between the kauniyah verses and the evidence of kauniyah (nature) that is spread out. Science seeks to explore the power of knowledge with its logic to the truth of the universe, while the Qur'an explains its concept of semiotics in exposing this naturalness. Between the two truths, the Qur'an is the most effective individual-social proselytizing solution in expounding its semiological communication. This study aims to uncover kauniyah verses through semiotic studies directed as a medium for individual-social proselytizing and its God. This research is a qualitative research using descriptive-analysis methods, namely researchers try to explain their research data and then analyze it in the form of a long description in obtaining the final conclusion. The results of the analysis of this paper are (1) there are similarities between the kauniyah verses and the form of the universe according to semiotic studies, and (2) the semiotics of the kauniyah verses into a solutive individual-social proselytizing communication between the truth of science and religion. The final conclusion is that semiotics is able to trace the truth of science and religion through the Qur'an so that it is able to present a solutive medium of proselytizing.